Audio reproduction for personal ambient home assistance: concepts and evaluations for normal-hearing and hearing-impaired persons. (September 2014) - Huber, Rainer; Meis, Markus; Klink, Karin; Bartsch, Christian; Bitzer, Joerg
<x xml:space="preserve">Abstract</x> Within the Lower Saxony Research Network Design of Environments for Ageing (GAL), a personal activity and household assistant (PAHA), an ambient reminder system, has been developed. One of its central output modality to interact with the user is sound. The study presented here evaluated three different system technologies for sound reproduction using up to five loudspeakers, including the "phantom source" concept. Moreover, a technology for hearing loss compensation for the mostly older users of the PAHA was implemented and evaluated. Evaluation experiments with 21 normal hearing and hearing impaired test subjects were carried out. The results show that after direct comparison of the sound presentation concepts, the presentation by the single TV speaker was most preferred, whereas the phantom source concept got the highest acceptance ratings as far as the general concept is concerned. The localization accuracy of the phantom source concept was good as long as the exact listening position was known to the algorithm and speech stimuli were used. Most subjects preferred the original signals over the pre-processed, dynamic-compressed signals, although processed speech was often described as being clearer.